CONDITIONS FOR THE FORMATION AND DEVELOPMENT OF FINANCIAL CENTERS IN NATIONAL ECONOMY - Khamdamova Sabina; Akhmadaliyeva Nikholakhon PhD (The Conference Hub, 2025)
This article explores the conditions for the formation and development of financial centers in the national economy, with a particular focus on Uzbekistan’s integration into the global financial system. It examines the importance of political stability, institutional and legislative reforms, and sophisticated financial infrastructure as the main foundations for creating financial hubs that are competitive. The contribution of global financial institutions like the World Bank and the Asian Development Bank to Uzbekistan's economic transition, investment climate, and long-term sustainable growth is given particular consideration.
Keywords: Financial centers, globalization, macroeconomic stability, financial infrastructure, international financial institutions, investment, Uzbekistan.